Sosialisasi Pentingnya Pendidikan Tinggi di Bidang Teknologi dalam Menyambut Era Society 5.0 - Sabinus Rainer N.Christi; Risma Petrus; Zulkarnain (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to socialize the importance of the role of Higher Education, especially Higher Education that is engaged in the field of technology in facing the era of society 5.0. This activity was attended by a number of class XII students at Yapis High School located in Manokwari Regency, West Papua. This activity was carried out well and received a positive response from the students of SMA Yapis Manokwari, this was marked by the active participation shown by the students in participating in the whole series of socialization activities, the existence of dialogic interaction between presenters and students, questions and answers and discussion.